The Economic Factors Affecting on Exchange Rate in the Lao PDR - PHIMPHACHANE, vilatda; INTHOULATH, Tularkham; MIXAYPHON, Niphaphone (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
The study of economic factors affecting on exchange rate in the Lao PDR is crucial for the economic system, particularly in areas such as international trade, import and export, and investment. This research aims to analyze key economic factors including money supply, inflation rate, interbank rate, foreign reserves, and current account that affecting on exchange rate in the Lao PDR especially exchange rate of Lao Kip against the US Dollar and Thai Baht. The study covers data from the 1st quarter of 2010 to the 4th quarter of 2023, encompassing 56 quarterly observations. The analysis is conducted using quantitative analysis through the Autoregressive Distributed Lag (ARDL) Model. The study found that the money supply, inflation rate and foreign reserves have positive relationship on the exchange rate of Lao Kip against both the US Dollar and the Thai Baht at significant level of 0.1, 0.05, 0.01 respectively. while the interbank rate has negative relationship on the exchange rate of Lao Kip against the Thai Baht at significant level of 0.01. However, the current account does not have a significant impact on the exchange rate of Lao Kip against either the US Dollar or the Thai Baht.